Financial convergence analysis: implication for insurance and pension markets - Kuznetsova, Natalia; Pisarenko, Zhanna V. (Business: Theory and Practice, 2016)
The proposed paper is one of a set of articles dedicated to the new phenomenon in the global and national financial markets – financial convergence – and is focused on theoretical issues. The hypothesis of the article is to argue whether the financial convergence determines the directions of financial market (namely, insurance and pension sectors) development. Adequately the goal of this paper is to analyze the existence of convergence processes in the insurance and pension markets. Methods of systematic and logical analysis are used. In the first part authors give brief history of the convergence phenomenon research. Then the paper analyses influence of financial convergence on insurance and pension markets, manifested in the following effects: mix of financial institutions functions; distribution channels advantages, increase of insurance and pension funds companies’ competitiveness; governance models convergence. The major results of the study are: demographic shifts in different developed and emerging markets countries caused the need to reform the social security systems and public pension schemes and refocus them to the market-based financial convergence model; pension funds, acting as institutional investors, are the leading players in the contemporary global financial market; competition at the financial market causes the expansion of a number of services offered by various organizations: banks, insurance companies, pension funds and so on, which offer a wide range of services not directly related to their core businesses; the mixing of financial institutions functions from the insurance, pension and banking sectors, increased competition for customers at the national and global financial market.